Mutations in RNA Methyltransferase Gene NSUN5 Confer High Risk of Outflow Tract Malformation - Wang, Yifeng; Jiang, Tao; Xu, Jiani; Gu, Yayun; Zhou, Yan; Lin, Yuan; Wu, Yifei; Li, Wei; Wang, Cheng; Shen, Bin; Mo, Xuming; Wang, Xiaowei; et al. (Frontiers in Cell and Developmental Biology, 2021)
NSUN5, encoding a cytosine-5 RNA methyltransferase and located in the 7q11.23 locus, is a candidate gene for tetralogy of Fallot (TOF). Deletion of the 7q11.23 locus in humans is linked to cardiac outflow tract (OFT) disorders including TOF. We identified four potential pathogenic mutations in the coding region of NSUN5 and which were enriched in TOF patients by an association study of 132 TOF patients and 2,000 in-house controls (P=1.44×10-5). We then generated a Nsun5 null (Nsun5-/-) mouse model to validate the human findings by defining the functions of Nsun5 in OFT morphogenesis. The OFT did not develop properly in the Nsun5 deletion embryonic heart. We found a misalignment of the aorta and septum defects caused by the delayed fusion of the membraneous ventricular spetum as an OFT development delay. This caused OFT development delay in 27 of 64 (42.2%) Nsun5-/- mice. Moreover, we also found OFT development delay in 8 of 51 (15.7%) Nsun5+/- mice. Further functional experiments showed that the loss of Nsun5 function impaired the 5-methylcytosine (m5C) modification and translation efficiency of essential cardiac genes. Nsun5 is required for normal OFT morphogenesis and it regulates the m5C modification of essential cardiac genes. Our findings suggest the involvement of NSUN5 in the pathogenesis of TOF.